2015
DOI: 10.1177/1948550614566858
|View full text |Cite
|
Sign up to set email alerts
|

Speaking Out of Both Sides of Their Mouths

Abstract: The ideologically objectionable premise model posits that biased political judgments can emerge across the political spectrum. Previous tests of ideological differences in political judgment biases have utilized between-subjects designs (i.e., separate comparisons). In this study ( N = 410), we examined whether these biases also emerge in within-subjects designs (i.e., joint comparisons) and compared the strengths of judgment biases in between-subjects and within-subjects designs. Across designs, both liberals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Participants rated their personal political orientation on a nine-point, vertical scale from (1) extremely conservative to (9) extremely liberal, with moderate as the mid-point (5) as was used in Jost et al, 2007. The political orientation item has often been included within demographics in previous research (Fitzgerald and Wickwire, 2012; Feinberg and Willer, 2013; Crawford et al, 2015; Janoff-Bulman and Carnes, 2016). The mean political orientation score was 5.65 ( SD = 2.17).…”
Section: Methodsmentioning
confidence: 99%
“…Participants rated their personal political orientation on a nine-point, vertical scale from (1) extremely conservative to (9) extremely liberal, with moderate as the mid-point (5) as was used in Jost et al, 2007. The political orientation item has often been included within demographics in previous research (Fitzgerald and Wickwire, 2012; Feinberg and Willer, 2013; Crawford et al, 2015; Janoff-Bulman and Carnes, 2016). The mean political orientation score was 5.65 ( SD = 2.17).…”
Section: Methodsmentioning
confidence: 99%
“…It is challenging to measure bias in a within-subjects design. People feel compelled to maintain consistency in their judgments, and insofar as they are reluctant to answer the same question in different ways, the design may preclude finding differences (see Uhlmann et al, 2009; Crawford et al, 2015; Winegard et al, 2018). Nonetheless, evidence of motivated change in judgments would contribute to the case that people furnish responses to free will questions partly to uphold moral responsibility.…”
Section: Studymentioning
confidence: 99%
“…For example, recent work using behavioural rather than self-report measures has found that cognitive flexibility is reduced in strong partisans on both sides of the political spectrum (Zmigrod et al, 2019). In this study, while social conservatism also predicted cognitive rigidity, this factor was much less influential than partisan extremity (also see Crawford, Kay, & Duke, 2015). Ryan and Aziz (2020) reported an experiment in which Democrats and Republicans were equally likely to endorse misleading rumours about political opponents.…”
Section: Discussionmentioning
confidence: 61%